Advances in conceptual modeling : ER 2018 Workshops Emp-ER, MoBiD, MREBA, QMMQ, SCME, Xi'an, China, October 22-25, 2018, Proceedings /: ER 2018 Workshops Emp-ER, MoBiD, MREBA, QMMQ, SCME, Xi'an, China, October 22-25, 2018, Proceedings. (2018) - Unknown
No abstract available